Electronic Ni–N interaction enhanced reductive amination on an N-doped porous carbon supported Ni catalyst. Issue 23 (2nd November 2022) - Song, Wenjing; Wan, Yujie; Li, Yuefeng; Luo, Xin; Fang, Weiping; Zheng, Quanxing; Ma, Pengfei; Zhang, Jianping; Lai, Weikun
Abstract : Reductive amination on Ni/N-doped porous carbon catalyst was enhanced by the formation of Ni–N x sites and the electronic interaction of N and Ni species, which promoted the reductive amination of CO bonds and reduced the activation energy. Abstract : Low cost and high efficiency catalysts for the reductive amination of carbonyl compounds are critical to the utilization of renewable biomass. In this paper, a highly efficient N-doped porous carbon supported Ni catalyst was prepared by a template-assisted pyrolysis and impregnation method. In the presence of NH3 and H2, the as-prepared catalyst could effectively catalyze the reductive amination of various carbonyl compounds into corresponding primary amines with high yield and excellent stability. Comprehensive characterization demonstrated that the reductive amination of furfural towards furfuryl amine was linked to the formation of Ni–N x sites and the electronic interaction of N and Ni species on the N-doped carbon surface, which promoted the reductive amination of CO bonds and significantly reduced the activation energy in reductive ammonolysis of trimers and Schiff base intermediates. This work provided a new insight into rational design of reductive amination catalysts for primary amine production.